El material didáctico y su relación con el aprendizaje de niños y niñas de inicial 2, del instituto particular “San Mateo” de la ciudad de Riobamba, período lectivo 2013 – 2014”. Lineamientos alternativos - Veloz Miño, María Fernanda (2014)
The objective of the present research is to analyze: “THE EDUCATIONAL MATERIAL AND ITS RELATION WITH THE TWO INICIAL EDUCATION CHILDREN LEARNING OF “SAN MATEO” PARTICULAR INSTITUTE FROM RIOBAMBA CITY, SCHOOL PERIOD 2013 - 2014”. An overall objectivefor this researchwas formulated: "To publicize the importance of the useofLearning Materialsin the 2InitialChildrenLearningof “San Mateo”particular Institute from Riobamba city, Period 2013 - 2014”. The scientific, inductive, analytical, descriptive and the statistical model were the methods used. The information was collected through a survey applied to the teachers and observation guide to children; in order to determine the effect in the educational materials in the learning and evaluate the main skills related with fields of learning. . The application ofthe surveydeterminedthat 100% of the teachersusedInstructional Materialsprovidedin itsdaily work. TheInstructional Materialsare the means bywhich the childand maketheir learningexperienceis for theseteachers todevelopobject manipulationusingdifferentclassesconsideringdifferent methods andtechniques. The application oftheObservation Guidewas determinedthat 90% of boys andgirlshaveseena pictureVerySatisfactorydevelopmentof thecore skillsof learning,and 10% of children have a Satisfactory box